Serious game for internal medical practice (crowd simulation) - Ching, Mah Yoke (2013)
Crowd simulation is now being widely used in various virtual environment applications such as entertainment, games and virtual environment. With the existing of crowd simulation in those applications can provide an immersive feeling into static scenes therefore elevate the realistic of the systems. The collision avoidance is important for a large number of characters in a same area, it used to prevent or avoid any collisions among character. Collision avoidance is one of the important elements that needed for construct crowd simulation. Besides that, steering is another important element for the simulation crowd system. By utilize this two elements, the application can produce higher level of realism of crowd simulation as well as make the applications more realistic and interesting. The comparison among different technique has been presented here.